1992
DOI: 10.1007/bf00130025
|View full text |Cite
|
Sign up to set email alerts
|

Control of C,N,P distribution in soils of riparian forests

Abstract: It is now well accepted that riparian forests have an important role in regulating upstream/downstream flow of matter and energy in river ecosystems. Since geomorphic processes determine the structure of channels and floodplains, we have investigated whether different geomorphic features of riparian forests had any effects on the ability of their soils to retain nutrients and organic carbon. Willow riparian forests were chosen within the annual floodplain of the Garonne River, southwest France, to represent tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 46 publications
1
68
0
1
Order By: Relevance
“…Riparian zones play an important role in controlling nutrient fluxes from terrestrial to stream ecosystems (Gregory 1991, Pinay et al 1992. Therefore, removal of riparian trees can also affect the in-stream flux of dissolved nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Riparian zones play an important role in controlling nutrient fluxes from terrestrial to stream ecosystems (Gregory 1991, Pinay et al 1992. Therefore, removal of riparian trees can also affect the in-stream flux of dissolved nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Labile P export was controlled more by water than by sediments, with 62-78% of the labile P in stormflow occurring as soluble P. Frink (1991) found that watershed models that included a sediment transport component tended to overestimate P export from agricultural watersheds and underestimate P export from wooded and urban watersheds and suggested that this was due to an underestimation of soluble P transport as predicted by these models. While the mechanisms associated with sediment removal are primarily geomorphological (Lowrance et al 1984, Pinay et al 1992, the mechanisms associated with dissolved P removal are primarily biogeochemical. For the remainder of this paper, we will limit our discussion of the P retention functions of forested wetlands to the biogeochemical pathways associated with dissoved phosphate removal.…”
Section: Wetland Resources Inmentioning
confidence: 99%
“…Soil can be polluted by wastewater irrigation. The metals in soils can also reach aquatic ecosystems by erosion and runoff from agricultural land (Pinay et al 1992). Soils contaminated in these ways may have an impact on water quality.…”
Section: Introductionmentioning
confidence: 99%